THE EFFECT OF SUPER OXIDE DISMUTASE (SOD) ON THE HEALING OF WHITE RAT CORNEAL EPITHELIAL WOUNDS CORNEAL EPITHELIAL WOUNDS: Oral Presentation - Experimental Study - Ophthalmologist - AGUNG DARMAWAN (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Keratitis and corneal erosion are part of eye trauma. Injury to the cornea will cause cell damage, triggering an inflammatory reaction that can increase the production of ROS (Reactive Oxygen Species). SOD (Superoxide Dismutase), one of the endogenous enzymatic antioxidants works by limiting the level of inflammation of the corneal damage caused by oxidation. Objective: Determine the effect of superoxide dismutase concentrations of 2%, 3%, 5% and placebo on the healing of corneal epithelial wound lesions in white rats with corneal trauma models Methods : Experimental study pre and post-test only with control group design in vivo with 24 samples of white wistar rats that met the inclusion and exclusion criteria. The research was conducted at the Animal House Laboratory, the Biotechnology Laboratory of the UNSRI Medical Faculty and the Eureka Research Center laboratory within 6 months. Results : 5% SOD showed a smaller reduction in wound area with the largest reduction (mean 0.67cm ± 0.007) followed by SOD 3% (mean 0.67cm ± 0.005). SOD 3% and 5% significantly correlated with weak strength at 48 hours and 72 hours. A significant reduction in the area of corneal epithelial wound lesions was only seen at 48 hours. Conclusion : SOD 5% most affected the healing of corneal epithelial wound lesions, followed by SOD 3%. SOD concentrations of 3% and 5% had a significant correlation on corneal epithelial wound healing at 48 and 72 hours with weak correlation strength.